Women's preference for cesarean delivery and differences between Taiwanese women undergoing different modes of delivery - Yeh Mei-Chiang; Hsu Chun-Sen; Tai Chen-Jei; Chu Kuei-Hui; Chien Li-Yin (BMC, 2010)
Abstract Background The rate of cesarean delivery was 35% in 2007 in Taiwan. It is unclear how many of the cesarean deliveries were without medical indications. Women's preference for cesarean delivery during their course of pregnancy has rarely been studied and therefore our objectives were to examine rate of cesarean deliveries without medical indications, to explore women's preference for cesarean delivery as their gestation advances, and to compare background and perinatal factors among women who underwent different modes of delivery in Taiwan. Methods This prospective study applied a longitudinal design. The study participants were 473 women who received prenatal care at four hospitals in Taipei and answered structured questionnaires at 20 to 24 weeks of pregnancy, 34 to 36 weeks of pregnancy, and 5 to 7 weeks after delivery. Results Of the 151 women (31.9%) who had cesarean deliveries, 19.9% were without medical indication. Three indications: malpresentation, prior cesarean section, and dysfunctional labor together accounted for 82.6% of cesarean section with medical indications. The prevalence of maternal preference for cesarean delivery was found to be 12.5% and 17.5% during the second and third trimester, respectively. Of the women who preferred cesarean delivery during the second trimester, 93.2% eventually had a cesarean delivery. Women who were older, with older spouses, and who had health problems before or during pregnancy were more likely to have cesarean deliveries. Conclusions About 20% of cesarean deliveries were without medical indications. Women's preference for cesarean delivery during the second trimester predicts subsequent cesarean delivery. Counseling regarding mode of delivery should be offered early in pregnancy, especially for women who are older or with older spouses, have health problems, or had a prior cesarean section.